Hormonal therapeutic strategy on the induction of accessory corpora lutea in relation to follicle size and on the increase of progesterone in sheep - Fernandez, Jimena (2018)
We determined the effect of GnRH or hCG treatment on day 4 post-time artificial insemination (FTAI) onthe formation of accessory corpora lutea (acc-CL) and on the concentration of serum progesterone (P4)insheep. Multiparous adult Merino ewes (n¼36) were synchronized for estrus using double injection ofPGF2aagonist (125mg Cloprostenol) with an interval of 14 days. At 53e56 h after the second PGapplication, FTAI was performed. On day 4 post FTAI, ewes were either treated with analogue of GnRH(4mg buserelin; n¼12) or hCG (300 IU, hCG; n¼12) or saline solution (1 ml; Control; n¼12). Twolaparoscopic ovarian examinations were performed on days 4 and 10 post FTAI. In thefirst observation,we determined the number of post ovulation corpora lutea (po-CL) and the site, number and diameter offollicles present in both ovaries. In the second laparoscopy, we observed the number of po-CL and acc-CL.The sizes of the follicles that generated the acc-CL were determined according to the position of thefollicles observed in thefirst laparoscopy. Serum P4concentration was determined on days 4, 7, 10, 13, 17and 21 post FTAI by chemiluminescence. A similar follicular population in size and number was observedin the three experimental groups prior to the beginning of treatments (Follicles 2 mm: 6.4±3.7, 3 mm:3.0±2.3, 4 mm: 1.1±0.5, 5 mm: 1.4±0.8; P˃0.05). The formation of 1.0±0.4 and 1.1±0.3 acc-CL wasobserved in the GnRH and hCG groups, respectively (P˃0.05), but was not observed in the Control group(P<0.05). Follicle sizes from which acc-CL generated were 3, 4 and 5 mm and did not differ betweenhormonal treatments (P˃0.05). The hCG group had higher mean concentrations of P4on days 7, 10, 13and 17 post FTAI compared with the GnRH group and the Control group (P<0.05), while no differenceswere observed between these two latter groups (P>0.05). Mean P4concentrations in ewes treated withhCG showed no differences according to the size of the follicle from which acc-CL were generated(P˃0.05). In conclusion, administration of hCG or GnRH on day 4 post FTAI induced the formation of oneacc-CL from follicles of 3, 4 or 5 mm, indistinctly. However, serum P4concentration increased signifi-cantly only in the hCG group. The serum P4concentrations of acc-CL that originated from different folliclesizes did not differ.